Problems Of Information Support In Designing The Development Of Hydrocarbon Deposits - Abdirazakov Akmal Ibrahimovich; Oripova Lobar Norboevna (Genius Journals, 2024)
This article provides information on the creation of a database and its integration with a mining and geological database in the oil and gas industry using database information
Keywords: information; oil and gas production; subsystems